Cardiac Function at Rest and During Exercise in Normals and in Patients with Coronary Heart Disease: Evaluation by Radionuclide Angiocardiography - Rerych, Stephen K. (1978)
This study demonstrates that radionuclide angiocardiography provides a simple and noninvasive approach for evaluation of myocardial function. Previous work concerning myocardial performance has been generally conducted with the patient in the supine position. Radionuclide angiocardiograms were performed in the present study at rest and during exercise in 30 normal subjects and in 30 patients with ischemic coronary artery disease. There were 30 normal controls (Group I), ten with single coronary artery disease (Group II), and 20 patients with multiple vessel coronary disease (Group III). All subjects were studied in the erect posture on a bicycle ergometer. In the normal controls, the mean heart rate doubled and the cardiac output tripled during exercise. Intensive training can lead to extraordinary levels of cardiac performance as shown in a world-class athlete who during peak exercise attained a heart rate of 210, an ejection fraction of 97%, and a cardiac output of 56 litres per minute. In the patients with coronary artery disease, both groups, were able to increase cardiac output to approximately twice the resting value. The magnitude of increase in blood pressure during exercise was not significantly different in the three groups. However, definite changes were present in the end-diastolic volume at rest was 116 and rose to 128 ml in Group I, 93 rising to 132 ml in Group II, and 138 increasing to 216 ml in Group III. The stroke volume increased comparably in all three groups, but the ejection fraction from rest to exercise showed a marked contrast in the controls compared to those with multivessel coronary disease. The ejection fraction rose in Group I from 66 to 80% during exercise, while in Group II it fell from 69 to 67%, and in Group III from 60 to 46%. These findings indicate that patients with ischemic myocardial disease respond to the stress of exercise by cardiac dilatation to maintain of increase stroke volume at increased heart rates. Moreover, the magnitude of this response appears to be greatest in patients with left main coronary artery stenosis. This approach for evaluating myocardial function during exercise provides useful data of importance in selecting medical versus surgical management of patients with ischemic coronary artery disease.